Cu-Ir thin film alloy as a potential substrate for the heteroepitaxial diamond growth; Materials Letters; Vol. 321 - Zenkin S. P. Sergey Petrovich; Gaydaychuk A. V. Alexander Valerievich; Mitulinsky A. S. Aleksandr Sergeevich; Linnik S. A. Stepan Andreevich (2022, 2022)
Title screen